2022
DOI: 10.2217/epi-2022-0179
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Networks Reveal Sex Differences in Gene Methylation, and Connections Between Maternal Risk Factors and Symptom Severity in Autism Spectrum Disorder

Abstract: Aim and methods: Artificial neural networks were used to unravel connections among blood gene methylation levels, sex, maternal risk factors and symptom severity evaluated using the Autism Diagnostic Observation Schedule 2 (ADOS-2) score in 58 children with autism spectrum disorder (ASD). Results: Methylation levels of MECP2, HTR1A and OXTR genes were connected to females, and those of EN2, BCL2 and RELN genes to males. High gestational weight gain, lack of folic acid supplements, advanced maternal age, preter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…We are aware of the limits of the present study in terms of sample size and monocentric nature of the study. Despite the Auto-CM system that we employed proved to be able to find reliable connections even in small datasets [ 31 , 32 , 33 , 34 , 37 , 68 , 69 , 70 ], replication of the present findings in larger cohorts is required both to confirm the observed associations and to test for the contribution of geographic, ethnic, genetic and region-specific environmental factors.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…We are aware of the limits of the present study in terms of sample size and monocentric nature of the study. Despite the Auto-CM system that we employed proved to be able to find reliable connections even in small datasets [ 31 , 32 , 33 , 34 , 37 , 68 , 69 , 70 ], replication of the present findings in larger cohorts is required both to confirm the observed associations and to test for the contribution of geographic, ethnic, genetic and region-specific environmental factors.…”
Section: Discussionmentioning
confidence: 78%
“…The added value of this approach in investigating biological systems is represented by its ability in evidencing the organizing principles of a network of variables and therefore to map biological processes using automatic and analytical models to reconstruct the imprecise, nonlinear and simultaneous pathways, underlying a complex set of data. In recent years, Auto-CM has been extensively applied to unravel the complexity of connections among environmental, clinical and biological variables in several medical datasets, leading to the identification of genetic and epigenetic biomarkers for neurodevelopmental disorders, cancer and lifestyle outcomes [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sex differences in RELN methylation were observed in the blood DNA of ASD individuals. Indeed, RELN methylation was higher in males than in females [ 48 ]. In ASD females, blood RELN methylation levels were inversely correlated with disease severity, as assessed through the ADOS-2 score [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In ASD females, blood RELN methylation levels were inversely correlated with disease severity, as assessed through the ADOS-2 score [ 38 ]. In males, blood RELN methylation levels were linked to the methylation levels of EN2 , a gene that protects dopaminergic neurons against mitochondrial insult from pesticides [ 48 ]. Reduced RELN in the mother can directly affect neurodevelopment of her offspring, or alternatively the hypermethylation profile can be “transmitted” to the fetus via maternal germline.…”
Section: Discussionmentioning
confidence: 99%
“…Such differences in the OXTR gene expression were also evident in the mRNA levels [ 62 ]. Furthermore, recent analyses on the use of artificial neural networks indicated that changes in methylation levels of the OXTR gene were specific to females with autism spectrum disorder [ 63 ].…”
Section: Oxtr In Mental Disordersmentioning
confidence: 99%